Straight from the heart : modern Norwegian cinema, 1971-1999 - Cowie, Peter; Holst, Jan Erik.; Blindheim, Astri Dehli (Kristiansund : Kom Forlag, 1999)
"Peter Cowie has followed the renaissance in Norwegian cinema since the early 1970s, [--] in this lavishly illustrated volume he describes the themes and personalities involved." [kansipaperi]
Filmografia, index.
Keywords: elokuvahistoria -- Norja; elokuvat -- Norja